2020
DOI: 10.3390/genes11080872
|View full text |Cite
|
Sign up to set email alerts
|

RNA Editing and Modifications in Mood Disorders

Abstract: Major depressive disorder (MDD) is a major health problem with significant limitations in functioning and well-being. The World Health Organization (WHO) evaluates MDD as one of the most disabling disorders in the world and with very high social cost. Great attention has been given to the study of the molecular mechanism underpinning MDD at the genetic, epigenetic and proteomic level. However, the importance of RNA modifications has attracted little attention until now in this field. RNA molecules are extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 92 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…The transition of A-to-I is processed by adenosine deaminases acting on RNA (ADAR) enzymes, which is a principal form of RNA editing 91 . It is reported that A-to-I is a key factor influencing RNA metabolism, such as miRNA processing 92 .…”
Section: The Interplay Between M 6 a And Other Epimentioning
confidence: 99%
“…The transition of A-to-I is processed by adenosine deaminases acting on RNA (ADAR) enzymes, which is a principal form of RNA editing 91 . It is reported that A-to-I is a key factor influencing RNA metabolism, such as miRNA processing 92 .…”
Section: The Interplay Between M 6 a And Other Epimentioning
confidence: 99%
“…Upon DHT binding, the AR interacts specifically with ARE I/II in the promoter region of ADAR2 (adenosine deaminases acting on RNA), inducing its repression [ 77 ]. ADAR2 is an RNA editing gene that encodes an enzyme whose function is to modify adenosine nucleotide into inosine by deamination [ 78 ]. Repression of ADAR2 results in an increase in circFNTA levels, which leads to an elevated sponging of the miR-370-3p; this miRNA bind directly to the farnesyltransferase (FNTA) mRNA 3’ UTR binding site to increase FNTA expression.…”
Section: Ar Signaling and Bladder Cancer Progressionmentioning
confidence: 99%
“…It may possible that in hyper active brain areas, the overactive NMDA receptors might be the target of low therapeutic doses of ketamine because their affinity for ketamine might be higher (Shaffer et al, 2019). While little differences in the affinity for ketamine were reported for the four subtypes of NMDA receptors (Yamakura et al, 2000), it is also possible that in TRD subjects, the receptors undergoing turnover may acquire higher affinity for S-ketamine as a consequence of an editing process (Barbon and Magri, 2020). It has been reported that the turnover of AMPA receptors may be stimulated by ketamine and by its metabolites (2R,6R)-HNK and (2S,6S)-HNK (Zanos et al, 2016;Ho et al, 2018).…”
Section: Subgenual Cingulate Regionmentioning
confidence: 99%